Seeking Legitimacy Through Knowledge Production: The Politics of Monitoring and Evaluation of the EU Trust Fund for Africa - Natalie Welfens; Saskia Bonjour (JCMS: Journal of Common Market Studies, 2022)
Monitoring and evaluation (M&E) is a form of expert knowledge that is central to migration governance. This article analyses M&E of the EU Trust Fund for Africa (EUTF), created in 2015 to `fight the root causes of migration'. Combining institutionalist accounts with practice theory, we examine whether M&E knowledge production served the instrumental purpose of assessing policy impact or mainly legitimated particular policy actors and positions. We find that M&E did not produce evidence on whether the EUTF met its objectives. However, in the context of the EU's multiple crises, M&E knowledge production served to seek legitimacy not only for the EUTF, but also for the further fusion of development and migration policies, and for the EU as a competent and transparent actor. Our analysis highlights that knowledge use and knowledge production are connected, and that M&E knowledge politics allow for the legitimation of both actors and policies.
Keywords: 330; EU Trust Fund for Africa; evaluation; knowledge production; legitimacy; monitoring